Phenomenon of Church-Religious and Secular Charity in the Urals in 1914-1918: The Ethno-Confessional Aspect - Elena Yu. Kazakova-Apkarimova; Olga S. Porshneva (RUDN Journal of Russian History)
Within their article, the authors consider the influence of church-religious and secular charity in the ethno-confessional environment of the Urals under the ongoing conditions of the First World War. Through their research, they have shown that there was clear interaction between the government and society in this regard, and that cooperation by representatives of ethno-confessional groups of the Urals were instrumental in helping the front, the needy, and the victims of the war. The institutional forms and social practices characterizing church-religious and secular charity in the Urals are considered from the perspective of the actor themselves, revealing the role of both collective and individual participants. The contribution of ethno-confessional public organizations of the Urals to the development of charity is also clearly shown; its main directions are characterized. The role of the Orthodox Church structures and congregations, Muslim and other ethno-confessional communities, women's associations, and individuals in wartime charitable activities is further considered as well. While the specificity of church-religious charity in the ethno-confessional environment is revealed, this charity included: material assistance, moral support to those in need, as well as measures aimed at solving social issues and maintaining stability in society. The authors, through their research, they have shown that through conditions of war, that the functions of previously existing charitable organizations expanded and that new ethno-confessional structures of charitable character appeared which responded to the challenges of the emergency period. The authors conclude that the ethno-confessional charitable organizations regularly interacted with local governments, public and state institutions, interactions which increased the effectiveness of their activities in the region during the period of the war.